Time to use the Potty A potty training book for boys and girls - Munro, Fiona (London Autumn, 2021)
"Meet twins Johnny and Jasmine. It's time they started to try and use a potty and to wear pants. They HAVE pants, but Johnny just puts his on Teddy while Jasmine uses her potty as a slide for her toys!"--Publisher's description
Scientific Notions
For children from 3 to 6 years old
Keywords: Scientific notions